The Distinction of Clinicopathological Characteristics, Treatment Strategy and Outcome in Colorectal Cancer Patients With Synchronous vs. Metachronous Bone Metastasis - Ma, Chen-xi; Guan, Xu; Wei, Ran; Wang, Song; Quan, Ji-chuan; Zhao, Zhi-xun; Chen, Hai-peng; Liu, Zheng; Jiang, Zheng; Wang, Xi-shan (Frontiers in Oncology, 2020)
Background: The impact of the timing of bone metastasis (BM) diagnosis on colorectal cancer (CRC) patients is unclear. Our study aimed to explore the differences in clinicopathological characteristics, treatments and prognosis between synchronous BM (SBM) and metachronous BM (MBM) from CRC. Methods: We retrospectively investigated clinical data of CRC patients with SBM or MBM from 2008 to 2017 at Chinese National Cancer Center. Cancer specific survival (CSS) after BM diagnosis was estimated using the Kaplan-Meier method. The multivariable COX regression model identified the prognostic factors of CSS. Results: Finally, 63 CRC patients with SBM and 138 CRC patients with MBM were identified. Compared to SBM from CRC, MBM significantly was more involving multiple bone lesions (63.0% vs. 7.9%; p<0.001), and more frequently originated from rectal cancer (60.9% vs. 41.3%; p=0.033). The therapeutic strategies in SBM and MBM group were contrasted including systemic treatment, bisphosphonates, radiotherapy and metastasectomy for BM. 85.5% of patients in MBM group and 25.4% of patients in SBM group underwent primary tumor resection at initial diagnosis (p<0.001). The median CSS was 11 months in both SBM and MBM group (p=0.556), yet MBM patients developed from CRC in early AJCC stage presented obviously longer survival than those from advanced stage. Furthermore, patients could have improved CSS from primary tumor resection while there might be no survival benefit from targeted therapy in both SBM and MBM groups. Bisphosphonates was associated with a better CSS for patients with SBM, while radiotherapy for BM was related to a better CSS for patients with MBM. Conclusion: The CRC patients in SBM and MBM group represented different clinicopathological characteristics and treatment modalities, which affected the prognosis in different ways. Distinct consideration for CRC patients with SBM and MBM in clinical decision making is required.